Practice Patterns for Sexual History-taking among Florida Nurses - Salimah El-Amin; Sandra Suther; Gebre-Egziabher Kiros; Khaing Zaw (University of North Florida, 2016)
Florida has some of the highest reported sexually transmitted disease (STD) rates in the country. STDs are a particular problem for minorities, women, and adolescents. Sexual history elicitation is a tool available to clinicians to assess patients' sexual risk behaviors and to counsel, test, and treat STDs. Nurses play an important role in caring for patients' sexual health problems, including unwanted pregnancies and STDs. We examined the sexual history-taking practices among advanced registered nurse practitioners (ARNPs) in Florida. We mailed an anonymous pencil-and- paper survey to measure sexual history-taking practices to a stratified random sample of 795 ARNPs. We analyzed the data with SPSS. Overall, 185 ARNPs completed the survey (23% response rate). We found that sexual history-taking practices varied. Approximately 71% of Florida ARNPs reported taking sexual histories. Targeted interventions are needed to increase sexual history-taking practices.